An Overview of Ontologies in Virtual Reality-Based Training for Healthcare Domain - Mohamad, Ummul Hanan; Ahmad, Mohammad Nazir; Benferdia, Youcef; Shapi'i, Azrulhizam; Bajuri, Mohd Yazid (Frontiers in Medicine, 2021)
Virtual reality (VR) is one of the state-of-the-art technological applications in the healthcare domain. One major aspect of VR applications in this domain includes virtual reality-based training (VRT), which simplifies the complicated visualization process of diagnosis, treatment, disease analysis, and prevention. However, not much is known on how well the domain knowledge is shared and considered in the development of VRT applications. A pertinent mechanism, known as ontology, has acted as an enabler towards making the domain knowledge more explicit. Hence, this paper presents an overview to reveal the basic concepts and explores the extent to which ontologies are used in VRT development for medical education and training in the healthcare domain. From this overview, a base of knowledge for VRT development is proposed to initiate a comprehensive strategy in creating an effective ontology design for VRT applications in the healthcare domain.